Towards quantitative demineralization imaging for the assessment of carious lesions based on PS-OCT - Golde Jonas (EPJ Web of Conferences, 2020)
Assessing the stage and progression of enamel demineralization non-invasively is of high interest in conservative dentistry. By examining tooth samples with suspected occlusal lesions, we show the potential of depolarization imaging based on polarization-sensitive optical coherence tomography for the assessment of carious lesions and validate the results by co-registered X-ray micro-computed tomography volumes.